Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Compute this limit of series:

$\displaystyle \lim_{n\rightarrow \infty} \frac{1}{n^{3}}\sum_{k=1}^{n-1}k^2 $

I used the definition of the definite integral

$\displaystyle \int_{a}^{b}f(x)dx=\lim_{n\rightarrow \infty} S_{n}$

where $\displaystyle f(x)=x^2$, $\displaystyle [a,b]=[0,1]$; since the function is continuous in $\displaystyle [0, 1]$ then it is certainly integrated.

$\displaystyle \int_{0}^{1}x^2dx=\lim_{n\rightarrow \infty} \sum_{k=1}^{n-1}\frac{1}{n}\ \left(\frac{k}{n}\right)^2=\lim_{n\rightarrow \infty} \frac{1}{n^3}\sum_{k=1}^{n-1}k^2$

We have:



$\displaystyle \lim_{n\rightarrow \infty} \frac{1}{n^{3}}\sum_{k=1}^{n-1}k^2 =\frac{1}{3}$

Any suggestions, please? This limit can be solved in other ways?


share|improve this question
add comment

4 Answers

up vote 5 down vote accepted

By induction, you can prove that

$\displaystyle \sum_{k = 1}^n k^2 = \frac{n(n + 1)(2n + 1)}{6}$


$\displaystyle \lim_{n \rightarrow \infty}\frac{1}{n^3}\sum_{k = 1}^{n - 1} k^2 = \lim_{n \rightarrow \infty}\frac{1}{n^3}\frac{(n - 1)(n)(2(n - 1) + 1)}{6} = \lim_{n \rightarrow \infty}\frac{1}{n^3}\frac{(n - 1)(n)(2n - 1)}{6} = \lim_{n \rightarrow \infty}\frac{2n^3 - 3n^2 + n}{6n^3}$

$\displaystyle \lim_{n \rightarrow \infty}\frac{1}{3} - \frac{1}{2n} + \frac{1}{6n^2} = \frac{1}{3}$

share|improve this answer
add comment

Well done. The Riemann sum argument was carried out efficiently.

For another way of solving the problem, we can use the fact that the sum $\sum_{k=1}^n k^2$ is given by the explicit formula $$\sum_{k=1}^n k^2=\frac{n(n+1)(2n+1)}{6}.$$
I have quoted the sum to $n$, because it is the standard version, but you can get the explicit formula for the sum to $n-1$ by making the obvious substitution.

There are many ways to prove the above formula. One way is by induction.

So (after the substitution) we want to find the limit of $$\frac{(n-1)(n)(2n-1)}{6n^3}.$$ Cancel an $n$, then divide top and bottom by $n^2$. We want $$\lim_{n\to\infty}\frac{\left(1-\frac{1}{n}\right)\left(2-\frac{1}{n}\right)}{6}.$$

Remark: For additional explicit "sums of powers" formulas, please see the Wikipedia article on Faulhaber's Formula.

share|improve this answer
add comment

What you have is fine. If one knows the formula $\sum_{k=1}^nk^2=\frac16n(n+1)(2n+1)$, one can avoid the integration:


so $$\lim_{n\rightarrow \infty} \frac{1}{n^{3}}\sum_{k=1}^{n-1}k^2=\lim_{n\to\infty}\frac{2-\frac3n+\frac1n}6=\frac13\;.$$

share|improve this answer
add comment

Also, if you know it, this is a straightforward application of Stoltz-Cezaro:

$$\lim_{n\rightarrow \infty} \frac{1}{n^{3}}\sum_{k=1}^{n-1}k^2=\lim_{n\rightarrow \infty} \frac{\sum_{k=1}^{n}k^2-\sum_{k=1}^{n-1}k^2}{(n+1)^{3}-n^3}= \lim_{n\rightarrow \infty} \frac{n^2}{3n^2+3n+1}=\frac{1}{3}$$

share|improve this answer
add comment

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.